Penerapan Sistem Informasi Akuntansi Berbasis Aplikasi Microsoft - Evita Yuningtyas; Moh. Halim; Rendy Mirwan Aspirandy (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the role of application-based AIS for UD. Meeting Sustenance. This research method is descriptive qualitative. The object of this research is UD. Meet Sustenance which is located in Yosomulyo, Kab. Banyuwangi. The results showed that the existing business processes at UD. Meeting Sustenance in the application application stage through a computer can be described with a Flowchart flow to facilitate identification of business processes. Conclusion, UD. Temu Rezeki has not yet implemented a computer-based accounting information system. Keywords: Accounting Information System (AIS), Sales System, Computer Application, MSME